The Development of the planning and architectural thought of the holy city of Kadhimia in line with the spirit of the time - كوثر, خولة كريم (Journal of Planner and Development, 2011)
The evolution of thought, planning for Urban Communities in the second half of the twentieth century, through several successive stages. He was thought of planning urban communities depends on identifying the general plan for land uses of the project area as a basis for drawing charts the physical, social, economic, and put the general plan for land uses based on the terms of reference set by the number of experts in the ministries and agencies. I have lived cities in the Arab-Muslim region, during the transition period the natural and historic environment, urban, sophisticated balanced ways mentioned in the cultural, social, inspired by the teachings of Islam and the customs and traditions of the Arab social, put forth a set of customs, laws and regulations harmonious own, distinct from the rest of the physical environments in the world. And contain any urban environment on the surface of this planet special features associated with social norms, cultural, economic and environmental associated with the physical environment or the other cities is the memory of communities taking into account the requirements of contemporary planning and urban development so that the interested nature of architectural and urban local and regional private, and establish the concept that what we build today will be a legacy for future generations, at the same time maintain the integration with the role of architectural heritage in the overall national development in general, and tourism development in particular